ANALYSIS OF THE ACTIVITIES OF INTERNATIONAL ECONOMIC ORGANIZATIONS - Kamolov, Dostonbek; Karimqulova, Oygul (Science technology&Digital finance, 2023)
This article will reflect on the origin, activities of international economic organizations, its development and its place in the life of society, as well as the main directions in which it is possible to maximize the development of economic organizations.